Clinical Features and Symptom Recovery on a Gluten-Free Diet in Canadian Adults with Celiac Disease. (2013) - Pulido, Olga; Zarkadas, Marion; Dubois, Sheila; MacIsaac, Krista; Cantin, Isabelle; La Vieille, Sébastien; Godefroy, Samuel; Rashid, Mohsin
Abstract : BACKGROUND: Celiac disease can present with mild or nongastrointestinal symptoms, and may escape timely recognition. The treatment of celiac disease involves a gluten-free diet, which is complex and challenging. OBJECTIVE: To evaluate clinical features and symptom recovery on a gluten-free diet in a Canadian adult celiac population. METHODS: All adult members (n=10, 693) of the two national celiac support organizations, the Canadian Celiac Association and Fondation québécoise de la maladie coeliaque, were surveyed using a questionnaire. RESULTS: A total of 5912 individuals (≥18 years of age) with biopsy-confirmed celiac disease and/or dermatitis herpetiformis completed the survey. The female to male ratio was 3:1, and mean (± SD) age at diagnosis was 45.2±16.4 years. Mean time to diagnosis after onset of symptoms was 12.0±14.4 years. Abdominal pain and bloating (84.9%), extreme weakness/tiredness (74.2%), diarrhea (71.7%) and anemia (67.8%) were the most commonly reported symptoms at the time of diagnosis. Many respondents continued to experience symptoms after being on a gluten-free diet for >5 years. Sex differences were reported in clinical features before diagnosis, recovery after being on gluten-free diet and perceived quality of life, with women experiencing more difficulties than men. CONCLUSIONS: Delays in diagnosis of celiac disease in Canada remain unacceptably long despite wider availability of serological screening tests. Many patients report continuing symptoms despite adhering to a gluten-free diet for >5 years, with women experiencing more symptoms and a lower recovery rate than men. Awareness of celiac disease needs improvement, and follow-up with a physician and a dietitian is essential for all patients with celiac disease.